Alignment of innovation diffusion and project management to increase logistics digitalization - Diana Daškevič; Aurelija Burinskienė (Business, Management and Economics Engineering, 2025)
Purpose – This paper examines how integrating Innovation Diffusion Theory (IDT)  with structured project management frameworks enhances digital technology adoption in  logistics, addressing challenges in ineffective implementation.